Climate Change and International Environmental Law: The Legal Implications of Global Agreements - Kemmala Dewi; Safiullah Aziz; Zara Ali (Yayasan Adra Karima Hubbi, 2026)
Background. Climate change constitutes a systemic global crisis that challenges the effectiveness and coherence of international environmental law. Successive global agreements have attempted to regulate greenhouse gas emissions and strengthen climate governance, yet significant gaps persist between normative commitments and actual environmental outcomes. Purpose. This study aims to analyze the legal implications of major global climate agreements and to evaluate how their design influences state responsibility, compliance mechanisms, and accountability structures within international environmental law. Method. The research employs a qualitative doctrinal approach combined with comparative legal analysis of key instruments, including the UNFCCC, the Kyoto Protocol, and the Paris Agreement, supported by selected case-based judicial review. Results. Findings indicate a structural transition from centralized, binding emission targets toward a decentralized governance model grounded in nationally determined contributions, transparency frameworks, and judicial internalization. Binding obligations correlate with clearer compliance within regulated jurisdictions, while flexible mechanisms enhance participation but depend heavily on domestic implementation. Conclusion. The study concludes that international climate agreements function as normative catalysts that reshape domestic legal systems and human rights discourse, yet their effectiveness remains contingent upon stronger accountability mechanisms and clearer legal drafting to ensure long-term environmental integrity.